Benin : Poverty Reduction Strategy Paper; Growth Strategy for Poverty Reduction. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Benin has been implementing a national poverty reduction strategy for sustainable human development. The government of Benin judiciously stressed the development of the social sector and improved governance to develop human resources and enhance the effectiveness of its actions so as to lay the foundations for sustainable human development. The sectoral strategies and policies growing out of the poverty reduction and growth strategy (SCRP) will be refined and/or readjusted to more clearly delineate the actions planned and thereby facilitate their implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet